Study on the spectrophotometric detection of free fatty acids in palm oil utilizing enzymatic reactions - Azeman, Nur Hidayah; Yusof, Nor Azah; Abdullah, Jaafar; Yunus, Robiah; Hamidon, Mohd Nizar; Hajian, Reza (MDPI, 2015)
In this paper, a comprehensive study has been made on the detection of free fatty acids (FFAs) in palm oil via an optical technique based on enzymatic aminolysis reactions. FFAs in crude palm oil (CPO) were converted into fatty hydroxamic acids (FHAs) in a biphasic lipid/aqueous medium in the presence of immobilized lipase. The colored compound formed after complexation between FHA and vanadium (V) ion solution was proportional to the FFA content in the CPO samples and was analyzed using a spectrophotometric method. In order to develop a rapid detection system, the parameters involved in the aminolysis process were studied. The utilization of immobilized lipase as catalyst during the aminolysis process offers simplicity in the product isolation and the possibility of conducting the process under extreme reaction conditions. A good agreement was found between the developed method using immobilized Thermomyces lanuginose lipase as catalyst for the aminolysis process and the Malaysian Palm Oil Board (MPOB) standard titration method (R2 = 0.9453).